Verbal Prefixes and Syntactic - Semantic Classification of Verbs in CROVALLEX - Mikelić Preradović, Nives; Boras, Damir; Lauc, Tomislava (2013)
In this paper we aim to describe the latest work on the syntactic-semantic classification of verbs in Croatian language. We tried to extract the specific semantics and function of verb prefixes in Croatian and capture these specific features in the Croatian verb valency lexicon CROVALLEX. The syntactic and semantic connection between base verbs and derived prefixed verbs is revealed and modelled as rules which contribute to the enrichment of the CROVALLEX lexicon.
Rad je kao predavanje prezentiran na skupu 17th WSEAS International Conference on Computers (COMPUTERS13), održanom od 16.-19.06.2013., Rhodes Island, Grčka.
Projekt MZOS
ENG